IMPLEMENTASI VPN (VIRTUAL PRIVATE NETWORK) DENGAN MENGGUNAKAN MIKROTIK ROUTER PADA YAYASAN PENDIDIKAN AL-BASYARIAH BOGOR - Muhamad Ryansyah; Numan Musyaffa (Jurnal Teknik Informatika C.I.T Medicom, 2020)
VPN is a connection between one network with another network privately through a public network. At Al-Basyariah Education Foundation is a school that has several buildings far apart. The problems faced today that are in several areas related to and communicating using flash and using file shares for those who already have their own LAN. Meanwhile, to connect with the main building and the branch building using the internet and email to send data and communicate. By using a VPN (Virtual Private Network) build a network using the PPTP (Point-To-Point Tunneling Protocol) method with the Mikrotik Router RB2011L then the main building and branch building can be connected. Thus the Al-Basyariah Education Foundation can be connected and can access computer networks anywhere via the internet.